Slam dunk - King, Donna, 1949- (Boston, MA : Scholastic, 2007)
Talented thirteen-year-old Ashlee Carson is the Tribeca Saints' top-scoring point guard. Ashlee is smart, too, but her mom worries that basketball is going to get in the way of her bright academic future. Ashlee will do anything for a chance to win a place on the National Youth basketball team-even if it means defying her mother and enlisting the help of her estranged father, a former professional basketball player.
Includes excerpt from: Kickoff by Donna King.
Keywords: Basketball players -- Juvenile fiction; Parent and child -- Juvenile fiction; Children of divorced parents -- Juvenile fiction; Basketball stories